2005
DOI: 10.1186/1476-7961-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE response to purified and recombinant allergens in latex allergy

Abstract: BackgroundIn recent years, allergy to natural rubber latex has emerged as a major allergy among certain occupational groups and patients with underlying diseases. The sensitization and development of latex allergy has been attributed to exposure to products containing residual latex proteins. Although improved manufacturing procedures resulted in a considerable reduction of new cases, the potential risk for some patient groups is still great. In addition the prevalent cross-reactivity of latex proteins with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 24 publications
0
7
1
3
Order By: Relevance
“…Hev b 5, Hev b 6.01 and Hev b 6.02 are the most frequently recognized recombinant molecules and are able to detect specific IgE in 71% of all sensitized patients tested positive on NRL extracts (table 2). These findings partly overlap with previous reports (73.1%) [38]. …”
Section: Discussioncontrasting
confidence: 57%
“…Hev b 5, Hev b 6.01 and Hev b 6.02 are the most frequently recognized recombinant molecules and are able to detect specific IgE in 71% of all sensitized patients tested positive on NRL extracts (table 2). These findings partly overlap with previous reports (73.1%) [38]. …”
Section: Discussioncontrasting
confidence: 57%
“…However, it seems more likely that this patient is sensitized to a clinically relevant NRL allergen component (Hev b 2, 12, or 13) which was not available for testing. Raulf-Heimsoth et al [3] and Kurup et al [12] have both shown that Hev b 2 and 13 are part of the primary allergen components involved in sensitizing health care workers. Patient No.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 15 molecularly characterized NRL Hev b allergens, Hev b 5 and b 6 seem to play a major role in sensitizing healthcare workers [30,42] and patients with respiratory symptoms [43]. Moreover, spina bifida patients typically show sensitization to Hev b 1 and b 3, but also to Hev b 5, b 6 [44] and b 7 [45], even if to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%